Meningkatkan Motivasi Dan Hasil Belajar Siswa Kelas 1 SD Kanisius Kintelan 1 Melalui Model PBL - Wijaya, Gata Pandu; Amelia, Maria Agustina; Sarwi, Marciana (Paedagogie, 2023)
This study aims to increase the motivation and learning outcomes of grade 1 students at Kanisius Kintelan 1 Elementary School by using the problem based learning (PBL) learning model in the subject of matematic in the independent curriculum. The research method used is Classroom Action Research (CAR), which includes two cycles. Each cycle consists of four stages, namely Planning (Planning), Implementation (Acting), Observation (Observing), Reflection (Reflecting). Collecting data using test techniques, questionnaires and observation. The research subjects were class I SD Kanisius Kintelan 1, totaling 13 students consisting of 5 male students and 8 female students. The results of observations show the problem of student activity and student disinterest in lecture learning. Actions carried out using the problem based learning model of learning. The results showed that there was an increase in activity from cycle I to cycle II of 46%, an increase in learning outcomes from cycle I to cycle II of 77%. So it can be concluded that the application of the Problem Based Learning learning model can increase learning motivation and learning outcomes of class I SD Kanisius Kintelan 1 Yogyakarta.